The effects of prebiotic, probiotic or synbiotic supplementation on overweight/obesity indicators: an umbrella review of the trials’ meta-analyses - Rasaei, Niloufar; Heidari, Mohammadreza; Esmaeili, Fataneh; Khosravi, Sepehr; Baeeri, Maryam; Tabatabaei-Malazy, Ozra; Emamgholipour, Solaleh (Frontiers in Endocrinology, 2024)
Background: There is controversial data on the effects of prebiotic, probiotic, or synbiotic supplementations on overweight/obesity indicators. Thus, we aimed to clarify this role of biotics through an umbrella review of the trials' meta-analyses.Methods: All meta-analyses of the clinical trials conducted on the impact of biotics on overweight/obesity indicators in general populations, pregnant women, and infants published until June 2023 in PubMed, Web of Sciences, Scopus, Embase, and Cochrane Library web databases included. The meta-analysis of observational and systematic review studies without meta-analysis were excluded. We reported the results by implementing the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) flowchart. The Assessment of Multiple Systematic Reviews-2 (AMSTAR2) and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) systems were used to assess the methodological quality and quality of evidence.Results: Overall, 97 meta-analysis studies were included. Most studies were conducted on the effect of probiotics in both genders. Consumption of prebiotic: 8-66 g/day, probiotic: 10 4 -1.35×10 15 colony-forming unit (CFU)/day, and synbiotic: 10 6 -1.5×10 11 CFU/day and 0.5-300 g/day for 2 to 104 weeks showed a favorable effect on the overweight/obesity indicators.Moreover, an inverse association was observed between biotics consumption and overweight/obesity risk in adults in most of the studies. Biotics did not show any beneficial effect on weight and body mass index (BMI) in pregnant women by 6.6×10 5 -10 10 CFU/day of probiotics during 1-25 weeks and 1×10 9 -112.5×10 9 CFU/capsule of synbiotics during 4-8 weeks. The effect of biotics on weight and BMI in infants is predominantly non-significant. Prebiotics and probiotics used in infancy were from 0.15 to 0.8 g/dL and 2×10 6 -6×10 9 CFU/day for 2-24 weeks, respectively.It seems biotics consumption can result in favorable impacts on some anthropometric indices of overweight/obesity (body weight, BMI, waist circumference) in the general population, without any significant effects on birth weight or weight gain during pregnancy and infancy. So, it is recommended to intake the biotics as complementary medications for reducing anthropometric indices of overweight/obese adults. However, more well-designed trials are needed to elucidate the anti-obesity effects of specific strains of probiotics.